2006
DOI: 10.1385/cbb:46:3:265
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Dependent Calcium Channels in Young and Old Human Red Cells

Abstract: Presence of subtypes of voltage-dependent Ca channels was investigated in young and old human red cells, employing immunological and flux-kinetics methods. Western blots showed specific reaction toward polyclonal rabbit antibodies raised against a highly conserved residue of alpha1 subunit of high-voltage activated Ca channels (pan alpha1) and against conserved residues of alpha1C and alpha1E subunits. No specific reaction was detected with antibodies against conserved residues of alpha1A, alpha1B, or alpha1D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…The dominant effect involves the activation of calcium influx through native calcium channels. Although their study did not involve RBCs, there is evidence of similar calcium channels in RBCs 47‐50. Taking this study into account, the SNP inhibition of calcium influx and activation of the Gardos channel may involve inhibition of these native calcium channels.…”
Section: Discussionmentioning
confidence: 79%
“…The dominant effect involves the activation of calcium influx through native calcium channels. Although their study did not involve RBCs, there is evidence of similar calcium channels in RBCs 47‐50. Taking this study into account, the SNP inhibition of calcium influx and activation of the Gardos channel may involve inhibition of these native calcium channels.…”
Section: Discussionmentioning
confidence: 79%
“…However, Cheung et al (8) have reported that Ca 2+ influx induced by Epo was insufficient to activate Ca 2+ -sensitive K + channels (Gardos channel). This strongly indicates the presence of multiple Ca 2+ uptake pathways in EPCs during differentiation (52). We have recently reported the presence of N -methyl- d -aspartate receptors (NMDARs) in human progenitor cells and have shown that these nonselective, ligand-gated cation channels mediate Ca 2+ uptake in EPCs (18, 35).…”
mentioning
confidence: 91%
“…Nevertheless, a few studies have given evidence that true Ca 2+ channels might also be present in the RBCs membrane. Even if the data regarding the exact nature of the Ca 2+ pathway are confusing, the presence of both L-type and R-type Ca 2+ channels subunits in RBCs membrane has been detected using western blots and tracers fluxes with adapted inhibitors (Romero et al, 2006). The group of Pedro Romero has also shown that the channel types appear to be different according to the RBC age.…”
Section: Non-selective Cation Channelmentioning
confidence: 99%